A multisite evaluation of antifungal use in critical care: implications for antifungal stewardship. Issue 3 (23rd June 2022) - Logan, C; Hemsley, C; Fife, A; Edgeworth, J; Mazzella, A; Wade, P; Goodman, A; Hopkins, P; Wyncoll, D; Ball, J; Planche, T; Schelenz, S; et al.
Abstract: Background: ICUs are settings of high antifungal consumption. There are few data on prescribing practices in ICUs to guide antifungal stewardship implementation in this setting. Methods: An antifungal therapy (AFT) service evaluation (15 May–19 November 2019) across ICUs at three London hospitals, evaluating consumption, prescribing rationale, post-prescription review, de-escalation and final invasive fungal infection (IFI) diagnostic classification. Results: Overall, 6.4% of ICU admissions (305/4781) received AFT, accounting for 11.41 days of therapy/100 occupied bed days (DOT/100 OBD). The dominant prescribing mode was empirical (41% of consumption), followed by targeted (22%), prophylaxis (18%), pre-emptive (12%) and non-invasive (7%). Echinocandins were the most commonly prescribed drug class (4.59 DOT/100 OBD). In total, 217 patients received AFT for suspected or confirmed IFI; 12%, 10% and 23% were classified as possible, probable or proven IFI, respectively. Hence, in 55%, IFI was unlikely. Proven IFI ( n = 50) was mostly invasive candidiasis (92%), of which 48% had been initiated on AFT empirically before yeast identification. Where on-site (1 → 3)-β-d -glucan (BDG) testing was available (1 day turnaround), in those with suspected but unproven invasive candidiasis, median (IQR) AFT duration was 10 (7–15) days with a positive BDG (≥80 pg/mL) versus 8 (5–9) days with a negative BDG (<80 pg/mL). Post-prescription review occurred in 79% of prescribing episodes (median time to review 1 [0–3] day). Where suspected IFI was not confirmed, 38% episodes were stopped and 4% de-escalated within 5 days. Conclusions: Achieving a better balance between promptly treating IFI patients and avoiding inappropriate antifungal prescribing in the ICU requires timely post-prescription review by specialist multidisciplinary teams and improved, evidence-based-risk prescribing strategies incorporating rapid diagnostics to guide AFT start and stop decisions.